EFEKTIVITAS PRAKTIKUM KANCING GENETIKA TERHADAP HASIL BELAJAR PSIKOMOTORIK MAHASISWA/I PENDIDIKAN BIOLOGI UINSU PADA MATERI PEWARISAN SIFAT - Miftahul Khairani; Afifah Zahra Simanungkalit; Dedek Azura; Fitriya Handayani; Hanifa Mawaddah (Kampus Akademik Publiser, 2024)
The concept of inheritance of traits in living things is one of the biology materials that students learn in grade IX studied by biology students. Based on the results of interviews with students at UIN North Sumatra, many students experience difficulties and conceptual errors in understanding the concept of genetics (inheritance of traits), such as misunderstandings about genetic and phenotypic traits that are considered the same. The genetic button practicum is used to make it easier for students to understand the concept of the material taught. This study aims to determine the effectiveness of the genetics button practicum on the psychomotor learning outcomes of students in inheritance materials at UIN North Sumatra. The design used in this study is a One-Shot Case Study design. The sample of this study is students of biology 1 UIN North Sumatra with a total of 31 students. The determination of the sample was carried out using a simple random sampling technique. The instruments used in this study are in the form of practicum guide sheets and performance assessments. The data analysis carried out in this study is the effectiveness ratio to find out how much percentage of targets are achieved against the targets that have been set in the implementation of practice. The results of the analysis showed that the first practicum had 88% classical completeness and a classical effectiveness ratio of 117.3% and in the second practicum the classical completeness was 85% and a classical effectiveness ratio of 113.3%. This means that the use of the genetic button practicum method is effective on the psychomotor learning outcomes of students in learning biology of trait inheritance material at UIN North Sumatra